The relationship between psychology and school. Some hypothesis from work experiences. - Brescia, Filomena; Conti, Isabella; De Bellonia, Marina; Giovannetti, Chiara; Guido, Danny; Izzo, Paolo; Nolè, Michela; Rosselli, Rossella; Sarubbo, Maria; Verducci, Luigi (Rivista di Psicologia Clinica, 2013)
This contribution, will propose a reflection on the relationship between psychology and school, in order to catch the demand addressed by the school context to psychologists, and analyze the function they have or they may have. We believe that reflecting on these issues would be usefull to a scientific discussion and would contribute to the construction of the psychologist’s identity, which is seen in different contexts, and in particular in the school, as an aspect on which to query and formulate hypotheses. We will propose some cases to create a literature on the psychological intervention in the school context. This contribution is the final product of a larger activity of reporting and exchange on our different experiences with the school. In fact we are a work group, founded one year ago, composed by psychologists linked by their present or former work in the school with different roles: psychologist, educator, AEC (educational and cultural assistant). We are also students in the same School of Specialization in Psychoanalytic Psychotherapy, at different school years, who share an interest in creating a connection between training and work, theory and technique, psychotherapy and clinical psychologyl intervention, and finally between the demand addressed by the school context and the psychology professional competences. We reckon and we hope to demonstrate that exploring the issues come out in our experiences with the school context, we can also greatly enrich our clinical and psychotherapy expertise.